L‐proline and betaine inhibit extracellular enzymes mediated abeta 1‐42 aggregation, oxidative stress, and toxicity. Issue 6 (9th September 2018) - Ismail, Tania; Vancha, Sushma Reddy; Kanapathipillai, Mathumai
Abstract: Extracellular amyloid plaques are characteristics of Alzheimer's disease (AD). The amyloid plaques mainly consist of amyloid‐β (abeta) fragments. Extracellular biomolecules play a key role in abeta aggregation and subsequent plaque formation during AD. Among them, extracellular enzymes are known to induce abeta aggregation by catalyzing the crosslinking of abeta proteins. Although several therapeutic strategies have been studied to combat AD, studies to treat extracellular enzymes mediated abeta aggregation and toxicity is not explored in detail yet. Here we study the potential of osmolyte molecules l‐proline and betaine to inhibit the abeta aggregation and toxicity promoted by extracellular enzymes transglutaminase and lysyl oxidase in vitro . Results reveal that l‐proline and betaine have the potential to inhibit extracellular matrix enzymes mediated abeta aggregation/fibril formation and toxicity and oxidative stress in brain endothelial cells. Hence osmolytes could have the potential to modulate the effects of extracellular molecules during AD. Abstract :